2020
DOI: 10.3390/app11010210
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of Oxygen Carrier Aided Combustion (OCAC) with Methane and PSA Off-Gas

Abstract: Oxygen carrier aided combustion (OCAC) is utilized to promote the combustion of relatively stable fuels already in the dense bed of bubbling fluidized beds by adding a new mechanism of fuel conversion, i.e., direct gas–solid reaction between the metal oxide and the fuel. Methane and a fuel gas mixture (PSA off-gas) consisting of H2, CH4 and CO were used as fuel. Two oxygen carrier bed materials—ilmenite and synthetic particles of calcium manganate—were investigated and compared to silica sand, an in this conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…A laboratory-scale experimental study demonstrated that the conversion of methane to a larger extent takes place inside the bed when an oxygen carrier is used, compared to with inert silica sand. This shows that the heterogenous solid-gas reaction is significant [33]. The oxygen carrier is also acting as an oxygen buffer, meaning that the boiler could be better at handling a sudden increase in fuel feed.…”
Section: Oxygen Carrier-aided Combustion (Ocac)mentioning
confidence: 97%
“…A laboratory-scale experimental study demonstrated that the conversion of methane to a larger extent takes place inside the bed when an oxygen carrier is used, compared to with inert silica sand. This shows that the heterogenous solid-gas reaction is significant [33]. The oxygen carrier is also acting as an oxygen buffer, meaning that the boiler could be better at handling a sudden increase in fuel feed.…”
Section: Oxygen Carrier-aided Combustion (Ocac)mentioning
confidence: 97%
“…Switching from inert sand to an active material improves the oxygen distribution in the combustor and reduces the concentration of unburned components in the off-gas . Additionally, this approach leads to lower NO emissions because the active material promotes fuel conversion within the bed, minimizing flame combustion in the freeboard . Oxygen carrier-aided combustion can be readily implemented in the existing combustors if the hydrodynamics with the new bed material can match the design specification.…”
Section: New Research Frontiersmentioning
confidence: 99%
“…322 Additionally, this approach leads to lower NO emissions because the active material promotes fuel conversion within the bed, minimizing flame combustion in the freeboard. 323 Oxygen carrier-aided combustion can be readily implemented in the existing combustors if the hydrodynamics with the new bed material can match the design specification. The attractiveness of this approach also arises from the application of inexpensive carriers, such as ilmenite, 322,324 steel converter slag, 325 or natural ores.…”
Section: New Research Frontiersmentioning
confidence: 99%
“…Apart from creating an oxygen buffer in the bed, the oxygen carrier also enables solid‐gas reactions that are less temperature‐dependent than flame combustion. Laboratory‐scale experiments have shown that methane can be converted in the bottom bed, where the temperature is too low for proper flame combustion 4 …”
Section: Introductionmentioning
confidence: 99%
“…Laboratory-scale experiments have shown that methane can be converted in the bottom bed, where the temperature is too low for proper flame combustion. 4 OCAC has been implemented in several biomass-fired and waste-to-energy (WtE) plants in Sweden. The implementation has been done with an ilmenite-based bed material commercialized by Improbed AB (a subsidiary of the utility company E.ON.).…”
mentioning
confidence: 99%